Penerapan Strategi Digital Marketing dalam Meningkatkan Penjualan Tahu Susu Antapani Cabang Galuh Mas di Karawang - Windy Aryani; Rieke Retnosary; Dini Yani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research on the Antapani Milk Tofu business aims to analyze and provide an explanation of the use of digital marketing on the impact of increasing sales. This case study was designed using a qualitative descriptive approach. Based on the results of in-depth interviews with three employees and five consumers, it was found that. The use of digital marketing as a promotional tool can increase sales for the Antapani Milk Tofu business, Galuh Mas Karawang Branch, this proves that digital marketing on Instagram social media accounts as a promotional tool and e-commerce messaging platform has a positive impact on sales with a wider target market and responsive. Customers are greatly helped by the delivery application, making it easier for them to carry out other activities both at home and at work. Fatigue from activities also provides time efficiency for customers to place orders without having to come to an outlet or shop. The approach needs to be taken in an attractive manner to followers of the official Tahu Susu Antapani account to provide information on special activities or promotions.